The The role of the accountability apparatus in the mediation of competition and psychological capital on-budget performance manager: Case study village governance in Aceh Province - Sufitrayati; Indriani, Mirna; Mukhlis; Abdullah, Syukriy (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The capital affect apparatus responsibility and budget performance. In addition, the influence of the accountability apparatus on the budget performance manager, and the role of the accountability apparatus in mediating the influence of competence and psychological capital on the budget manager's performance. This study employs a design of explanatory research (hypothesis testing) with a causal method to explain the causal relationship (impact) between variables using hypothesis testing in order to meet its objectives. The proportionate stratified random sampling method was utilized in this investigation, with a total sample size of 350 respondents. Structural equation modeling is used in the analysis. The results obtained in this study are (1) competency (X1) effect on apparatus accountability (Z); (2) psychological capital (X2) does not affect apparatus accountability (Z); (3) competency (X1) affect the budget performance manager (Y); (4) psychological capital (X2) affect the budget performance manager(Y); (5) apparatus accountability (Z) affect the budget performance manager (Y); (6) the accountability apparatus is proven to be able to act as a mediating variable in the influence of competency on the budget performance management; and (7) apparatus accountability is not proven to act as a mediating variable in the influence of psychological capital on budget manager performance.